Does This COVID-19 Pandemic Demand a Scale Up in AEFI Reporting in India? - Sadhvika Kanagat; Abhijit Vinodrao Boratne; A. Suguna; Sinthu Sarathamani (Indian Association of Preventive and Social Medicine, 2022)
The COVID-19 Pandemic has changed the global picture in the field of public health in the past few years. This critical time has made life very uncertain for everyone. Man has been constantly striving to discover measures to stop the spread of this deadly virus; the COVID-19 vaccine is one such endeavour. The fear and anxiety towards a new vaccine is high among the general public. With every new vaccination, constant monitoring and documentation of the vital happenings is very important. Thus, the reporting of Adverse events following immunization (AEFI) needs to be strengthened and implemented more efficiently to analyse the efficacy of this vaccination drive with respect to protection from the disease without causing any harmful adverse effects.